Challenges of Addressing Money Laundering As A Threat To National Security: A Study of Nigeria and Senegal - Umar Sanda Babashani (Bulletin of Islamic Research, 2026)
Purpose – This study examines the challenges of addressing money laundering as a threat to national security in Nigeria and Senegal. The research was undertaken to assess how institutional weaknesses, regulatory fragmentation, and technological adaptation by criminal networks undermine the effectiveness of anti-money laundering and counter-terrorist financing (AML/CFT) frameworks in both countries. Design/methods/approach – The study adopts a qualitative comparative research design based exclusively on secondary data. Data were collected from FATF, GIABA, UNODC, national legislation, institutional reports, and peer-reviewed literature. Institutional Theory served as the principal analytical framework, complemented by Systems Theory, while qualitative thematic and comparative analyses were employed to evaluate legal frameworks, institutional coordination, enforcement practices, and national security implications. Findings – The findings reveal that Nigeria records high volumes of AML investigations and Suspicious Transaction Reports (STRs), yet conviction rates remain disproportionately low due to institutional fragmentation, political interference, and weak inter-agency coordination. Senegal demonstrates relatively stronger institutional coherence following FATF delisting, but enforcement effectiveness remains constrained by limited capacity and low detection rates. Both countries remain vulnerable to cash-based laundering systems, porous borders, and emerging digital and cryptocurrency channels. Research implications/limitations – The study relies solely on secondary data and focuses on two West African countries, which may limit the generalisability of findings to other regions. Variations in institutional reporting standards and data availability also affected comparative assessment. Originality/value – This study contributes to the literature by positioning money laundering as an institutional and systemic national security challenge rather than merely a financial crime issue. It provides comparative insights into AML governance in West Africa and highlights the need for institutional consolidation, technological upgrading, and regional cooperation.